Plasmonic Electrons‐Driven Solar‐to‐Hydrocarbon Conversion over Au NR@ZnO Core‐Shell Nanostructures. Issue 11 (6th April 2020) - Shen, Jinni; Chen, Zhenye; Han, Shitong; Zhang, Hongwen; Xu, Hailing; Xu, Chao; Ding, Zhengxin; Yuan, Rusheng; Chen, Jinquan; Long, Jinlin
Abstract: This work demonstrates the long‐range redox reactivity of gold plasmon‐generated hot electrons for solar‐driven CO2 conversion. A series of Au NR@ZnO core‐shell photocatalysts with a tunable shell thickness are rationally designed to achieve the solar‐to‐CH4 conversion, where the hot plasmonic electrons‐induced photoreduction takes place on the polar oxide moiety. The shell thickness‐independent activity implies that the core, gold nanorods, plays a dominant role in the CH4 generation. The ZnO metal oxide semiconductor shell is beneficial to prolong the lifetime of hot electrons, thereby enhancing the photocatalytic efficiency. However, the thickness of ZnO shell is not relevant to the production rate. Both of these two parts are co‐excited by solar light and synergetic enhance the photocatalytic activity. Abstract : It's the core that matters : A series of Au@ZnO core‐shell photocatalysts with a tunable shell thickness achieve the solar‐to‐CH4 conversion. The shell thickness‐independent activity implies that the core, gold nanorods, plays a dominant role in the CH4 generation and the ZnO shell is of advantage to prolong the lifetime of hot electrons which also enhance photocatalytic efficiency. However, ZnO shell thickness is not relevant to the production rate.